Analysis of independence and creative thinking skills of students through assignment - Kusmiyati Kusmiyati (Jurnal Pijar Mipa, 2022)
This study aims to describe students' independence and creative thinking skills through assignments. The subjects of this research are Biology Education students who take the Nutrition Science elective course as many as 20 people. Independence and creative thinking data were collected using an instrument with a Likert scale. The collected data were analyzed qualitatively into five categories. The results of the independence analysis showed as many as 16 students (80%) in the very good category and 4 students (20%) in the good category. The results of the creative thinking analysis showed as many as 13 students (65%) in the very good category and 7 students (35%) in the good category. It can be concluded that most of the students completing lecture assignments have independence and creative thinking skills in the very good category. The achievement of independence on the indicators of not depending on others, self-confidence, self-initiative, and self-control, each student varied from fairly good, good, and very good categories. Meanwhile, the achievement of independence for the indicators of discipline and responsibility varies in the good and very good categories. (c) The achievement of all indicators of students' creative thinking skills varies in the very good and good categories. The very good category was mostly achieved by students on the indicators of flexible and original thinking skills. In contrast, students mostly achieved the good category on the indicators of evaluation thinking skills.